Conformational properties of trimethyl phosphate monomer - Reva, Igor (2005)
Conformational isomerism of trimethylphosphate (TMP) has been studied de novo. TMP monomers were isolated in low temperature xenon matrices at different substrate temperatures and characterized using FTIR spectroscopy. At the lowest temperature, three different conformers, with overall molecular symmetries C3, C1 and Cs, were shown to co-exist in the matrix. Increase of the sample temperature led to conformational cooling, with the two minor conformers being depopulated successively, following an order of increasing stability. Initially, the less stable Cs conformer converted to the C1 form and, at higher temperatures, the C1 conformer converted to the global energy minimum, C3. Interpretation of the experimental data was supported by extensive calculations of the vibrational spectra and barriers to the conformational interconversion.